1997
DOI: 10.1093/toxsci/37.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methimazole, an FMO Substrate and Competitive Inhibitor, on the Neurotoxicity of 3,3′-Iminodipropionitrile in Male Rats

Abstract: This study was designed to examine the role of flavin-containing monooxygenase (FMO) on the auditory and vestibular neurotoxicity of 3,3'-iminodipropionitrile (IDPN) using the FMO substrate and competitive inhibitor methimazole (MMI). Specifically, the purpose was to block the FMO-mediated conversion of IDPN to the putative neurotoxic metabolite N-hydroxy3,3'-iminodipropionitrile (HOIDPN). In three separate experiments, adult male Long-Evans hooded rats were administered (ip) saline (vehicle), MMI, IDPN, or HO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…The chemical inhibitors used were as follows: methimazole for FMOs (Nace et al 1997;Kim & Ziegler 2000), imipramine for FMO1 (Dixit & Roche 1984;Cashman, 2000), and trimethylamine for FMO3 (Lang & Rettie 2000). DMA was incubated with rat liver microsomal protein (1 mg ml −1 ) in the presence of each inhibitor.…”
Section: Chemical Inhibitionmentioning
confidence: 99%
“…The chemical inhibitors used were as follows: methimazole for FMOs (Nace et al 1997;Kim & Ziegler 2000), imipramine for FMO1 (Dixit & Roche 1984;Cashman, 2000), and trimethylamine for FMO3 (Lang & Rettie 2000). DMA was incubated with rat liver microsomal protein (1 mg ml −1 ) in the presence of each inhibitor.…”
Section: Chemical Inhibitionmentioning
confidence: 99%
“…The vestibular and auditory neurotoxicities that result after administration of IDPN are also attributed to FMO-catalyzed conversion of the compound to the putative N-hydroxy-3,39-iminodipropionitrile (HOIDPN; Fig. 2B) (Jacobson et al, 1987;Morandi et al, 1987;Nace et al, 1997). This proposal is based on the fact that coadministration of methimazole, an FMO1/FMO3 inhibitor, with IDPN prevents these IDPN-mediated adverse events.…”
Section: Flavin-containing Monooxygenasesmentioning
confidence: 99%
“…Evidence that the vestibular toxicity depends on CYP bioactivation is also available for allylnitrile (Boadas-Vaello et al, 2009), but the ototoxic metabolite has not been identified. In the case of IDPN, the data available support the conclusion that flavin monooxygenase-mediated generation of N-hydroxy-IDPN is a bioactivation step (Morandi et al, 1987;Nace et al, 1997), but conclusive identification of the ototoxic metabolite is lacking.…”
Section: Discussionmentioning
confidence: 99%